Hybrid Forms of Business: The Logic of Gift in the Commercial World - Grassl, Wolfgang 1955- (2011)
Benedict XVI in Caritas in Veritate advances a positive view of businesses that are hybrids between several traditional categories. He expects that the “logic of gift” that animates civil society infuses the market and the State with relations typical for it—reciprocity, gratuitousness, and solidarity. His theological rationale offers an answer to two questions that have largely remained open in the literature—why hybridization of business occurs and why it is desirable. A rational reconstruction of hybrid enterprise that goes beyond a simple taxonomy of types benefits from the Pope’s call for an intrinsic integration of institutions and processes traditionally attributed to disparate spheres. The relational model of the Trinity defines the unity in diversity that accounts for the benefits of truly hybrid businesses, and the “logic of gift” serves as the agent of integration.
Keywords: Logic of gift; Social Enterprise; Reciprocity; Non-profit enterprise; Hybrid businesses; Holy Trinity; Caritas in Veritate; Catholic Social Teaching; Benedict XVI